2016
DOI: 10.1080/13669877.2015.1121904
|View full text |Cite
|
Sign up to set email alerts
|

Household adoption of smog protective behavior: a comparison between two Chinese cities

Abstract: This study compares residents of two Chinese cities -one with a high risk and one with a low risk of air pollution, in terms of their smog experience, reliance on smog information sources, risk perception, attribution of responsibility and intention for adoption of protective behavior regarding smog. The results indicate that the two cities differ considerably in their smog experience, somewhat less so in reliance on smog information sources and risk perception, and very little in protective behavior. Using mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 68 publications
(73 reference statements)
1
16
0
Order By: Relevance
“…The concern for disaster risk reduction and concern for building safety can be seen as risk perception. Similar to most of the prior studies, risk perception is a positive predictor of individual disaster preparedness (Bronfman et al, 2016;Han et al, 2017b;Han and Nigg, 2011;Sadiq and Graham, 2016;Zhang et al, 2010).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The concern for disaster risk reduction and concern for building safety can be seen as risk perception. Similar to most of the prior studies, risk perception is a positive predictor of individual disaster preparedness (Bronfman et al, 2016;Han et al, 2017b;Han and Nigg, 2011;Sadiq and Graham, 2016;Zhang et al, 2010).…”
Section: Discussionsupporting
confidence: 69%
“…This indicates that most of the public is aware of the earthquake risk in their region. The results also demonstrated that hazard proximity is positively correlated with hazard (earthquake) preparedness (Bonaiuto et al, 2016;Howe, 2011;Lindell, 2013;Mishra et al, 2010;Russell et al, 1995;Zhang et al, 2010).…”
Section: Discussionmentioning
confidence: 80%
“…Third, our research was limited to Wuhan, a densely populated and highly polluted city in the central Hubei province. Research by Wei, Zhu, Marinova, and Wang (2015) suggests that individuals' air pollution appraisals depend in part on where they live. More specifically, Wei et al (2015) found that individuals are most sensitive to air pollution when they live in a city that is not typically polluted.…”
Section: Future Directions and Limitationsmentioning
confidence: 99%
“…Research by Wei, Zhu, Marinova, and Wang (2015) suggests that individuals' air pollution appraisals depend in part on where they live. More specifically, Wei et al (2015) found that individuals are most sensitive to air pollution when they live in a city that is not typically polluted. In other words, their paper suggests that individuals might become psychologically desensitized to air pollution over time.…”
Section: Future Directions and Limitationsmentioning
confidence: 99%
“…(3) public awareness of smog pollution in China [12][13][14][15][16]; (4) the public's willingness to pay (WTP) for reducing or tracking haze pollution [17][18][19][20][21][22]; (5) the public's adaptive behavior responses to haze pollution in urban China [23,24]; (6) personal protection strategies from haze pollution [23,25]; and (7) consumers' purchase intentions related to products that deal with haze pollution [26].…”
Section: Introductionmentioning
confidence: 99%